334 Phase II study evaluating a chemokine-modulatory (CKM) regimen in patients with colorectal cancer (CRC) metastatic to the liver. (9th November 2020) - Mukherjee, Sarbajit; Boland, Patrick; Gupta, Medhavi; Grimm, Melissa; Attwood, Kristopher; Kalinski, Pawel
Abstract : Background: CRC remains the 2nd most common cause of cancer-related death in the US. Hepatic metastases develop in 20–50% of CRC patients. 1 Median overall survival (OS) of patients with metastatic CRC is poor, even with the advent of biologics. A high density of CRC-infiltrating effector cytotoxic T lymphocytes (Teff; CTL) is known to predict long-term outcomes and the responsiveness of tumors to immune checkpoint inhibitors (ICI). In our ex vivo tumor explant models and CRC-bearing experimental animals, the combination of toll-like receptor-3 (TLR3) ligands with interferon (IFN)-α with cyclooxygenase (COX)-2 inhibitors resulted in increased production of Teff attracting chemokines CXCL10 and CCL5, along with suppression of regulatory T cells (Treg) attracting chemokine, CCL22 in the tumor microenvironment. 2, 3 A combination of all three factors was needed to uniformly elevate the desirable chemokines and counteract CCL22 induction. Based on these studies and on prior clinical safety data, we developed this phase IIa study combining IFNα2b, celecoxib (COX-2 inhibitor) and rintatolimod (selective TLR3 agonist) as a chemokine-modulating (CKM) regimen for CRC patients with unresectable liver-metastatic disease. We aim to study the immunological impact, potential clinical efficacy and safety of this CKM regimen in a non-randomized, single-arm prospective phase II trial. Methods: Eligible patients have recurrent/metastatic unresectable CRC with hepatic metastases that are amenable to biopsy. Enrolled patients have prior treatment with or contra-indication to a fluoropyrimidine, irinotecan, oxaliplatin, anti-VEGF treatment, and an anti-EGFR targeted therapy (if RAS wt), as well as a PD-1 or PD-L1 targeted drug if MSI-H/dMMR. Patients receive celecoxib (200 mg orally PO BID), IFNα2b IV (20 million units/m2 IV QD), and rintatolimod (200 mg IV QD) on days 1, 2, 3, 8, 9, 10, 15, 16 and 17 in the absence of disease progression or unacceptable toxicity. Response assessment via liver biopsies (pre-treatment and on D20) and CT imaging (RECIST v1.1) on D46. If stable disease/response is demonstrated during repeat CT imaging, patients will continue to follow-up with CT imaging q8 weeks until progression, clinical deterioration, or withdrawal from the study. Primary endpoint assessment compares the change in CD8+ T-cells before treatment, with that seen post-treatment (measured by quantitative RT-PCR and expressed as a ratio of CD8α to a housekeeping gene). Secondary endpoints include objective response rate and safety profile. Subjects are monitored continuously for safety, based on Bayesian analysis. Exploratory endpoints include progression-free survival and overall survival. With a sample size of n=12 evaluable pts, the study design has a 90% power to detect a 0.77 standard deviation increase (pre- to post treatment) at a significance level of 0.1. Results: N/A Conclusions: N/A Trial Registration: ClinicalTrials. gov Identifier: NCT03403634 . Ethics Approval: The study was approved by Roswell Park Comprehensive Cancer Center's Institutional Review Board, approval number: MOD00006722/I-52917. Consent: N/A References: Lahr C.J, et al., A multifactorial analysis of prognostic factors in patients with liver metastases from colorectal carcinoma. J Clin Oncol, 1983. 1(11): p. 720–6. Muthuswamy R, et al. NF-κB hyperactivation in tumor tissues allows tumor-selective reprogramming of the chemokine microenvironment to enhance the recruitment of cytolytic T effector cells. Cancer Res . 2012;72(15):3735–3743. Obermajer N, et al. Promoting the accumulation of tumor-specific T cells in tumor tissues by dendritic cell vaccines and chemokine-modulating agents. Nat Protoc 13, 335–357 ( 2018).